2023
DOI: 10.1186/s12909-023-04023-8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Project ECHO® for Pain: implementation and mixed methods evaluation of a virtual medical education program to support interprofessional pain management in children and youth

Abstract: Background Pediatric pain is a complex health challenge requiring a multi-modal management approach. It is critical that healthcare providers (HCPs) have access to ongoing, flexible education and mentorship specific to pediatric pain. However, there are significant gaps in available pain education and a need for more opportunities to support interprofessional training. Project Extension for Community Healthcare Outcomes (Project ECHO®) is a model for delivering online HCP education and cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…18 Virtual community such as the Project Extension for Community Healthcare Outcomes (Project ECHO®) can enhance the capabilities of primary teams. 19 PPC services can also be developed in the absence of a dedicated PPC physician. A study led in Saudi Arabia, the implementation of a nurse-led service was found to be an option.…”
Section: Myth 5: Providing Ppc Is Costly and Requires Specialized Res...mentioning
confidence: 99%
“…18 Virtual community such as the Project Extension for Community Healthcare Outcomes (Project ECHO®) can enhance the capabilities of primary teams. 19 PPC services can also be developed in the absence of a dedicated PPC physician. A study led in Saudi Arabia, the implementation of a nurse-led service was found to be an option.…”
Section: Myth 5: Providing Ppc Is Costly and Requires Specialized Res...mentioning
confidence: 99%
“…Nurses in particular play a significant role in pain management due to spending more time at the patient's bedside. 10 According to previous studies, the lack of knowledge in care providers is the significant barrier to optimal pain management. 11 12 The evidence shows…”
Section: Introductionmentioning
confidence: 99%
“…Nurses in particular play a significant role in pain management due to spending more time at the patient’s bedside. 10 According to previous studies, the lack of knowledge in care providers is the significant barrier to optimal pain management. 11 12 The evidence shows that care providers’ knowledge of pain management and their perceived responsibility are significantly related to the organisation’s policies.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric ECHO® For Pain , based in Ontario Canada, is one of the largest pediatric pain-focused ECHO® programs in the world ( 26 ). Program scope is inclusive of multimodal, evidence-based approaches to support interdisciplinary management of pediatric acute, chronic, and transitional pain.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, this program has delivered more than 100 TeleECHO clinics to an interprofessional audience of over 1,800 HCPs from 27 different disciplines. These TeleECHO clinics are associated with significant improvements in interprofessional HCP pain knowledge and self-efficacy as well as positive practice impacts ( 26 ).…”
Section: Introductionmentioning
confidence: 99%